Chronic urotensin-II infusion induces diastolic dysfunction and enhances collagen production in rats - Lavinia Tran (2018)
The vasoactive peptide urotensin-II (U-II) is likely to play a key causal role in cardiac remodeling that ultimately leads to heart failure. Its contribution, specifically to the development of diastolic dysfunction and the downstream intracellular signaling, however, remains unresolved. This study interrogates the effect of chronic U-II infusion in normal rats on cardiac structure and function. The contribution of Rho kinase (ROCK) signaling to these pathophysiological changes is evaluated in cell culture studies. Chronic high-dose U-II infusion over 4 wk signifi-cantly impaired diastolic function in rats on echocardiography-derived Doppler indexes, including E-wave deceleration time (vehicle 56.7 ± 3.3 ms, U-II 118.0 ± 21.5 ms; P < 0.01) and mitral valve annulus peak early/late diastolic tissue velocity (vehicle 2.01 ± 0.19 ms, U-II 1.04 ± 0.25 ms; P < 0.01). A lower dose of U-II infusion (1 nmol·kg-1· h-1) yielded comparable changes. Diastolic dysfunction was accompanied by molecular [significant increases in procollagen-α1(I) gene expression on real-time PCR] and morphological (increases in total collagen, P < 0.05, and collagen type-I protein deposition, P < 0.001) evidence of left ventricular (LV) fibrosis following high-dose U-II infusion. The ROCK inhibitor GSK-576371 (10-7to 10-5M) elicited concentration-dependent inhibition of U-II (10-7M)-stimulated cardiac fibroblast collagen synthesis and cardiac myocyte protein synthesis. Chronic U-II infusion causes diastolic dysfunction, caused by fibrosis of the LV. The in vitro data suggest that this may be in part occurring via a ROCK-dependent pathway. Copyright © 2010 the American Physiological Society.